Contrasting effects of selective MAGL and FAAH inhibition on dopamine depletion and GDNF expression in a chronic MPTP mouse model of Parkinson's disease. (November 2017) - Pasquarelli, Noemi; Porazik, Christoph; Bayer, Hanna; Buck, Eva; Schildknecht, Stefan; Weydt, Patrick; Witting, Anke; Ferger, Boris
Abstract: The modulation of the brain endocannabinoid system has been identified as an option to treat neurodegenerative diseases including Parkinson's disease (PD). Especially the elevation of endocannabinoid levels by inhibition of hydrolytic degradation represents a valuable approach. To evaluate whether monoacylglycerol lipase (MAGL) or fatty acid amide hydrolase (FAAH) inhibition could be beneficial for PD, we examined in parallel the therapeutic potential of the highly selective MAGL inhibitor KML29 elevating 2-arachidonoylglyerol (2-AG) levels and the highly selective FAAH inhibitor PF-3845 elevating anandamide (AEA) levels in a chronic methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine/probenecid (MPTP/probenecid) mouse model of PD. Chronic administration of KML29 (10 mg/kg) but not PF-3845 (10 mg/kg) attenuated striatal MPTP/probenecid-induced dopamine depletion. Furthermore, KML29 induced an increase in Gdnf but not Bdnf expression, whereas PF-3845 decreased the MPTP/probenecid-induced Cnr2 expression without any effects on neurotrophin expression. Investigation of treatment-naïve striatal mRNA levels revealed a high presence of Gdnf and Mgll in contrast to Bdnf and Faah . Treatment of primary mouse microglia with 2-AG increased Gdnf but not Bdnf expression, suggesting that microglia might mediate the observed KML29-induced increase in Gdnf . In summary, pharmacological MAGL but not FAAH inhibition in the chronic MPTP/probenecid model attenuated the MPTP/probenecid-induced effects on striatal dopamine levels which were accompanied by an increase in 2-AG levels. Highlights: MAGL but not FAAH inhibition attenuates dopamine depletion in a chronic MPTP model. MAGL but not FAAH inhibition further increases GDNF expression in chronic MPTP mice. 2-AG treatment of primary microglia increases GDNF expression. CB2 expression is decreased upon FAAH inhibition in chronic MPTP mice.